2017
DOI: 10.1097/md.0000000000006370
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-1β and interleukin-1receptor antagonist polymorphisms in Egyptian children with febrile seizures

Abstract: Febrile seizure is the most common seizure disorder of childhood. Of the pro-inflammatory cytokines, interleukin-1 is defined as the first endogenous pyrogen.We designed this study to investigate single-nucleotide polymorphisms (SNPs) situated at positions –31 (C/T), and –511 (C/T) of interleukin-1beta (IL-1β) gene promoter and interleukin-1receptor antagonist (IL-1RA) gene variable number of tandem repeats in intron 2 (VNTR); to determine whether these polymorphisms could be a marker of susceptibility to febr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 39 publications
1
20
0
Order By: Relevance
“…The IL-1β-31 variant involves a TATA-box polymorphism that markedly affects DNA-protein interactions in vitro 25. T allele of IL-1β-511 reportedly up-regulates promotor activity, consequently increasing IL-1β production both in vitro and in vivo 926. The present study found near-complete LD between IL-1β-31 and IL-1β-511 variants, similar to a study of adult gastric cancer 25.…”
Section: Discussionsupporting
confidence: 83%
“…The IL-1β-31 variant involves a TATA-box polymorphism that markedly affects DNA-protein interactions in vitro 25. T allele of IL-1β-511 reportedly up-regulates promotor activity, consequently increasing IL-1β production both in vitro and in vivo 926. The present study found near-complete LD between IL-1β-31 and IL-1β-511 variants, similar to a study of adult gastric cancer 25.…”
Section: Discussionsupporting
confidence: 83%
“…The interleukin 1 receptor antagonist (IL-1RA), controlling the IL-1, is an anti-inflammatory protein. Studies indicate a relationship between the overexpression of IL-1β and an imbalance between IL-1β and IL-1RA and FS (20)(21)(22) . Increased IL-1 and tumour necrosis factor (TNF) levels in response to exogenous pyrogens stimulate an increase in the levels of interleukin 6 (IL-6).…”
Section: Immune Factors -Cytokinesmentioning
confidence: 99%
“…Little has been reported with respect to inflammatory cytokines and enzymes. However, two papers investigating single-nucleotide polymorphisms of interleukin 1β (IL-1β) in patients with febrile seizures have raised the possibility of de novo mutations [86,87]. They found that IL-1β TT genotypes were over-represented in febrile seizure–experiencing groups compared with healthy controls.…”
Section: Molecular Mechanisms Of Epilepsymentioning
confidence: 99%